English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-12-12 15:59:36 · 6 answers · asked by Kesari 1 in Science & Mathematics Mathematics

Sorry it should be

If x = 3^(1/3) + 3^(-1/3) then x^3 - 3x = ?

2006-12-12 16:20:58 · update #1

6 answers

x = 3^(1/3) + 3^(1/3)
x = 2 * 3^(1/3)

x^3 = (2 * 3^(1/3))^3
x^3 = 2^3 * 3^(1/3)^3
x^3 = 8 * 3^(3 * 1/3)
x^3 = 8 * 3^1
x^3 = 24

3x = 3 * 2 * 3^(1/3)
3x = 6 * 3^(1/3)

x^3 - 3x = 24 - 6 * 3^(1/3)
x^3 - 3x = 6 ( 4 - 3^(1/3) )

2006-12-12 16:09:30 · answer #1 · answered by Puzzling 7 · 0 0

If x = 3^(1/3) + 3^(1/3) then x^3 - 3x = ?

x = 3^(1/3) + 3^(1/3)
x = 2*3^(1/3) or in decimal form
x = 2.884499141, so

x^3 - 3x =
(2.884499141)^3 - 3(2.884499141) = 15.34650259, or


x^3 - 3x = ? Plug in 2*3^(1/3) for x

(2*3^(1/3))^3 - 3(2*3^(1/3)) =

24 - 6*3^(1/3) =

-6*3^(1/3) + 24 = 15.34650258

2006-12-13 00:19:38 · answer #2 · answered by Pam 5 · 0 0

x=2,
so 2^3-6= 8-6=2

2006-12-13 00:02:51 · answer #3 · answered by oolala597 1 · 0 1

x = 3^(1/3) + 3^(1/3) = 2 [3^(1/3)]

x^3 - 3x = {2[3^(1/3)]}^3 - 3 [2(3^(1/3)] = 8(3) - 6[3^(1/3)] = 24 - 6[3^(1/3)] = 6 [ 4-3^(1/3)]

2006-12-13 00:08:42 · answer #4 · answered by Srinivas c 2 · 0 0

x = 3^(1/3) + 3^(1/3) =2*3^(1/3)
x^3=(2*3^(1/3))^3=8*3=24
3x=6*3^(1/3)
x^3-3x=24-6*3(1/3)=15.3465

2006-12-13 00:24:29 · answer #5 · answered by yupchagee 7 · 0 0

x=3^(1/3)+3^(1/3)
x=2.884499141

then

(2.884499141)^3 - 3(2.884499141) = 15.34650258

2006-12-13 00:03:28 · answer #6 · answered by aznfobboytly 3 · 0 0

fedest.com, questions and answers